Sense of safety or meaning in danger? Real-contact stick fighting as an imagistic ritual - Pauha, Teemu (Frontiers in Psychology, 2024)
It is a common assumption that human behavior is guided by a desire to feel safe and avoid harm. However, this view is challenged by the popularity of high-risk leisure sport and other practices that involve subjecting oneself to a considerable danger with no apparent gain. By using real-contact stick fighting as an example, I suggest that the attractiveness of at least some such practices can be explained by cognitive dynamics that are typical of affectively intense rituals such as initiations. Affectively intense rituals are known to enhance personal meaning-making and foster identity fusion, that is, the overlapping of personal and social identities. The sense of meaning thus engendered effectively satisfies common identity motives and thus elicits positive affect. By introducing ritual studies perspectives into the edgework paradigm that is commonly used to conceptualize voluntary risk taking, I contribute to an increased understanding of the cognitive processes motivating participation in extreme leisure sport.